Emerging Trends in Midwest Bobwhite Culture - Thomas V. Dailey (National Quail Symposium Proceedings, 2017)
In the Southeastern United States, Breeding Bird Surveys that bobwhite populations have been declining at 3.8%/year over the last 3 decades. Declines have been attributed the cumulative effects of large-scale deterioration of quail habitat quality associated with advanced succession, intensive monoculture farming, and intensive timber management. Additional factors such as changing role of predation, expansion of red imported fire ants, and metapopulation processes may exacerbate declines. Declining bobwhite hunter participation, changing public values, and realignment of conservation emphases have diminished the emphasis on bobwhite management nationally. However, within the Southeast 3 states, Virginia, Georgia, and North Carolina, have developed targeted private lands initiatives to enhance local and regional bobwhite habitats and populations. Additional opportunities exist for enhancing regional populations through broad avian conservation initiatives such as the North American Bird Conservation Initiative and Partners in Flight. Potential benefits from these regional efforts will be accrued only if greater value and emphases are placed on conservation of early successional habitats. As anthropogenic activities and natural successional processes influence regional usable space for bobwhite in the Southeast, established paradigms regarding relationships among predation, harvest, habitat management, and population dynamics may no longer be germane. Restoration of local and regional bobwhite populations will require a much greater understanding of bobwhite population processes at a mechanistic level across local and regional spatial scales.
Keywords: Colinus virginianus; land use; northern bobwhite; Southeast; trends